THE ROLE OF PARENTS IN FORMING THE MOTIVATION OF PRESCHOOL CHILDREN TO JOIN RIDING (Physical Culture and Sport: Scientific Perspective, 2023)
In recent years, children's equestrianism and pony sports have been actively developing in Ukraine. Special children's equestrian competitions have become increasingly popular, allowing preschool-age riders to participate. This age is crucial for laying the foundations of a child's physical and mental health, as well as shaping their motives and attitudes towards physical culture and sports. Adults, particularly parents, play a significant role in this process of surrounding the child. To popularize equestrianism among children and involve preschoolers in this type of physical activity, it is necessary to understand the specific role of parents in motivating children to interact with horses. The aim of this research is to provide a detailed analysis of the influence of parents on the motivation of preschool children for equestrian activities and determine the factors that contribute to the child's development in this field. The following methods were used during the scientific research: analysis of scientific literature and online resources; surveying (questionnaires) and pedagogical observation, comparison, correlation and generalization, mathematical statistical methods. The research showed that parents play an extremely important role in shaping the motivation of preschool-aged children to interact with horses and engage in equestrian activities. Parents' positive attitude towards horses, as well as their own desire to experience equestrianism, contribute to a more effective involvement of children in this form of physical activity. In such cases, parents encourage their children to interact with the animals, actively communicate and support them during training, and provide assistance as needed. On the other hand, adults' expressions of fear towards horses, whether conveyed verbally or non-verbally to children, can lead to a child's refusal to interact with animals and engage in equestrian activities.
Keywords: equestrian sport; children's involvement; parental influence; attitudes towards animals; physical activity